Ventral lateral parietal cortex and episodic memory retrieval. (October 2018) - Rugg, Michael D.; King, Danielle R.
Abstract: With the advent of functional neuroimaging it quickly became apparent that successful episodic memory retrieval was consistently associated with enhanced activity in ventral lateral parietal cortex (VLPC), especially the left angular gyrus. Here, we selectively review recent neuropsychological and functional neuroimaging evidence relevant to the question of the functional significance of this activity. We argue that the balance of the evidence suggests that the angular gyrus supports the representation of retrieved episodic information, and that this likely reflects a more general role for the region in representing multi-modal and multi-domain information.